2014
DOI: 10.1111/bjd.13194
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of hand eczema in adolescence: report from BAMSE – a population‐based birth cohort

Abstract: At the age of 16 years, the 1-year prevalence of hand eczema was substantial, with an incidence rate of the same magnitude as in adults. Female predominance was seen in adolescence. It is preferable that the occurrence of hand eczema is reported by adolescents themselves, as they are the ones most aware of their symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 30 publications
4
40
0
2
Order By: Relevance
“…[7][8][9] Interestingly, selfreported data from a Swedish population-based birth cohort including 16-year old adolescents, found an incidence rate of 5.7/1000 person-years, 10 which is almost the same ratio as in adults, illustrating the early onset of the disease. [7][8][9] Interestingly, selfreported data from a Swedish population-based birth cohort including 16-year old adolescents, found an incidence rate of 5.7/1000 person-years, 10 which is almost the same ratio as in adults, illustrating the early onset of the disease.…”
Section: Epidemiologymentioning
confidence: 99%
“…[7][8][9] Interestingly, selfreported data from a Swedish population-based birth cohort including 16-year old adolescents, found an incidence rate of 5.7/1000 person-years, 10 which is almost the same ratio as in adults, illustrating the early onset of the disease. [7][8][9] Interestingly, selfreported data from a Swedish population-based birth cohort including 16-year old adolescents, found an incidence rate of 5.7/1000 person-years, 10 which is almost the same ratio as in adults, illustrating the early onset of the disease.…”
Section: Epidemiologymentioning
confidence: 99%
“…Anderson using the hand eczema extent score (HEES) method. Measuring the extent of the eczema is accepted as a measure of severity [4,5]. The maximum score is 74 points (both hands): a score of 0 is considered symptomless, 1-3 very mild, 4-5 mild, 6-12 moderate and ≥13 severe hand eczema [5].…”
Section: Examination Of Extent Of Hand Eczemamentioning
confidence: 99%
“…The degree of hand eczema is variable and measuring the extent of the eczema is accepted as a measure of severity [4,5]. The severity of hand eczema correlates to the presence of Staphylococcus aureus [6], but the cause and effect relationship has not been clearly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate of hand eczema in adolescence is of the same magnitude as in adults (573/100 000 person‐years) and we have recently found that the 1‐year period prevalence of hand eczema is 5·2% among Swedish adolescents . Hand eczema (dermatitis on the hands) is often long‐lasting, severely affecting quality of life and working capacity .…”
mentioning
confidence: 99%